First-principle calculations of magnetic properties of Ho6(Fe, Mn)Bi2 compounds - Garcia-Adeva, Angel J.; Apiñaniz, Estibaliz; Herrero, Aritz; Aseguinolaza, Ivan R.; Oleaga, Alberto (Rare metals, 2024)
The magnetic properties of Ho 6 MnBi 2 and Ho 6 FeBi 2 crystals are investigated by means of density functional theory. These materials are currently an active subject of research in the context of magnetic refrigeration applications since they exhibit a remarkable magnetocaloric effect. In this work, the equation of state, density of states and magnetic moments are calculated and compared with previous experimental results for these materials. Also, the Curie temperatures for the paramagnetic to ferromagnetic phase transition observed in these systems are calculated from first principles. All the calculated quantities are in reasonable agreement with experimental data, which suggests that density functional theory could provide a reliable framework to theoretically investigate the magnetic properties of intermetallic ternary compounds. Graphical abstract